Makna Pernyataan נִחַם יְהוָה עַל־זֹאת (niHam yhwh (ädönäy) al-zöt ) Dalam Amos 7:3 dan 6 - Anon Dwi Saputro; Julio Avner Oktavianus Faot (Sekolah Tinggi Teologi Bethel Ambon, 2021)
This article explain the statement of God’s regret in Amos 7: 3 and 6. This research uses a word study research method and a literary approach by paying attention to prophetic literature in the sub-genre of judgment. This study aims to explore the meaning and get the correct application of God's statement of regret. Some interpreters such as Thomas L. Constable, Jeff Niehaus, B. J. Boland etc. only emphasized the side of repentance and God's change of mind on the evil of Israel. But that word has nothing to do with repenting or turning to God. Immediately this statement was expressed only by the grace of God. The word